Volume 5A: Heat Transfer 2019
DOI: 10.1115/gt2019-90180
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of Shaped Hole Film Cooling With the Influence of Cross Flow

Abstract: In the modern highly-loaded gas turbine, due to the large pressure difference between the suction side and the pressure side of the turbine blade, strong cross flow is formed and it strongly affects the aerodynamic and cooling performances in the end-wall region. The film cooling behavior in the environment of strong cross flow is different from the straight channel environment widely studied in the literature. In this research, the effect of cross flow on film cooling is investigated by Large Eddy Simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In order to select the appropriate turbulence model for the film cooling simulations, three different turbulence models: realizable k−ϵ model (Shih et al, 1995), shear stress transport (SST) model (Menter, 1994), and transitional SST model (Langtry and Menter, 2009), are initially selected and employed to obtain the numerical simulation results, respectively. The numerical simulation results of the laterally averaged film cooling effectiveness are further validated with the experimental results obtained from our previous works (Li et al, 2018;Wang et al, 2019), as shown in Figure 7. It can be seen that the realizable k−ϵ model performs the best compared with the experimental results and thus is selected as the turbulence model for the following numerical simulations.…”
Section: Figuresupporting
confidence: 78%
See 2 more Smart Citations
“…In order to select the appropriate turbulence model for the film cooling simulations, three different turbulence models: realizable k−ϵ model (Shih et al, 1995), shear stress transport (SST) model (Menter, 1994), and transitional SST model (Langtry and Menter, 2009), are initially selected and employed to obtain the numerical simulation results, respectively. The numerical simulation results of the laterally averaged film cooling effectiveness are further validated with the experimental results obtained from our previous works (Li et al, 2018;Wang et al, 2019), as shown in Figure 7. It can be seen that the realizable k−ϵ model performs the best compared with the experimental results and thus is selected as the turbulence model for the following numerical simulations.…”
Section: Figuresupporting
confidence: 78%
“…In order to address this difficulty, a curved tunnel is designed to solely provide the lateral pressure gradient for film cooling, as shown in Figure 1B. A curved tunnel with a constant width is adopted (Li et al, 2018;Wang et al, 2019), which is determined from the real dimension of the experimental facility. Compared with the ideal flat plate, the lateral pressure gradient is one of the most significant characteristics in the curve tunnel environment.…”
Section: Research Objectmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that the reason for the decrease in the effectiveness at high Mach numbers was the separation and large-scale oscillation of the coolant in the hole. Furthermore, Wang, Su, and Yuan (2020) studied the effect of the cross-flow on the film cooling process on an end wall and the flow fields of a 7-7-7 shaped hole with the LES Smagorinsky-Lilly model [17]. The cross-flow caused the counter-rotating vortex pair (CRVP) to be asymmetric.…”
Section: Introductionmentioning
confidence: 99%